Outcome of Primary Intracerebral Hemorrhage: A Study in Tertiary Care Center - Rajbanshi, Jagat Narayan; Nepal, Pankaj Raj (Eastern Green Neurosurgery, 2020)
Background: Intracerebral hemorrhage (ICH) is an irreversible phenomenon inside the brain parenchyma resulting in mild to severe neurological deficit. Based on etiology it is broadly divided into primary and secondary. Primary ICH is usually due to the rupture of Charcot-Bouchard aneurysm and chronic hypertension. Charcot – Bouchard aneurysms are supposed to get formed due to lipohyalinosis. With the aim to evaluate the outcome of primary ICH admitted to our institute this study is performed.Materials and methods: This is a prospective analytical study, where all the consecutive patients of the primary ICH were collected. Quantitative variables like age, the volume of hematoma, midline shift, GCS, and systolic blood pressure (SBP) were presented as mean and standard deviation (S.D). Whereas, qualitative variables like gender, site, and side of hematoma, type of treatment, best motor response were presented in frequency and percentage. The outcome of the patient was measured using the Glasgow outcome scale (GOS) and the association between qualitative/quantitative variables and GOS was done using the chi-square test or Fischer exact test whenever applicable in SPSS20.Results: There were a total of 31 patients with a mean age of 59.81(S. D 15.8) year and male predominance (74%). The mean volume of hematoma was 40 ml. Similarly, midline shift ranged from zero to 14 mm. The majority of primary ICH were located in basal ganglia (35%) and on the right side (52%). The mean GCS at presentation was 12.1 (S.D 2.166). Mean Systolic blood pressure was 163.77 mmHg (S.D 34.6 mmHg) with maximum SBP up to 240mmHg. There was a 14% mortality in this study group with favorable outcome (GOS 4 and 5) in 82%. GOS was significantly associated with the volume of hematoma and midline shift.Conclusion: The outcome of primary ICH is strongly associated with the volume of hematoma and midline shift. They were generally associated with hypertension with a mean systolic blood pressure of >160 mm Hg.